Elements of motivation that contributes toward employees performance of Negeri Roadstone Sdn Bhd / Danial Iffatul Anis Ismail and Nur Atiqah Saafi - Ismail, Danial Iffatul Anis; Saafi, Nur Atiqah (Faculty of Business and Management, 2013)
The purpose of this research is to find the elements that motivate the Negeri Roadstone Sdn Bhd staff at the workplace. The dependent variable is employees‟ performance and independent variables are reward system, working conditions, career advancement and job security. This research is being conducted at Negeri Roadstone Sdn Bhd. In completing this research, about 60 questionnaires have been distributed to the respondents. The respondents are included all the staff in Negeri Roadstone Sdn Bhd. In order to get the result for this research, the researcher has used SPSS program to analyze data from the information gathered. To analyze the data, the researcher has been used Reliability Analysis, Cross Tabulation Analysis, Frequency Distribution and Descriptive Statistic by using SPSS Program. From the findings, the researcher indicates that the most of the respondents agree that working environment is the most elements that motivate them at the workplace. Second is the job security, while third is career advancement. Reward system that is the least factor that motivates the employee at the workplace.